An experimental test of a compensatory nest predation model following lethal control of an overabundant native species. (March 2019) - Beggs, Richard; Pierson, Jennifer; Tulloch, Ayesha I.T.; Blanchard, Wade; Westgate, Martin J.; Lindenmayer, David
Abstract: Culling of overabundant and invasive species to manage their ecological impacts on target species is widely practised but outcomes are unpredictable and monitoring of effectiveness often poor. Culling must improve ecosystem function, so clear, measurable goals, such as improved breeding potential of target species, are necessary. Many overabundant and invasive species are also nest predators and nest predation is the principal cause of breeding failure of many birds of conservation concern. It is important for managers to know the likely effects on nest predation when culling one species among a suite of nest predatory species. We tested the effect of culling a hyperaggressive, overabundant bird and known nesting disruptor, the noisy miner ( Manorina melanocephala ), on artificial nest predation rates in remnant eucalypt woodlands in a highly fragmented agricultural landscape of eastern Australia. Culling of noisy miners is already practised to manage this key threatening process, but evidence of improved breeding outcomes for target species is lacking. We found no significant change in artificial nest predation rates following the treatment, despite a 28% reduction in noisy miner abundance in treatment compared to control sites. We identified five other nest predatory bird species, the noisy miner being responsible for 18.3% of total predation. Our findings suggest a compensatory nest predation model, which is problematic for management. It means that, where culling is done with a view to improving breeding potential of target species by reducing nest predation, removing one nest predatory species may not result in a commensurate reduction in nest predation. Graphical abstract: Unlabelled Image Highlights: Culling noisy miners did not reduce artificial nest predation rates. Noisy miners were responsible for 18% of artificial nest predation. Five other bird species were recorded predating nests. Compensatory nest predation seems to be operating in this landscape. Culling noisy miners may not improve breeding potential of target species.